Design and evaluation of nonfluorous CO2-soluble oligomers and polymers. - Wang, Y; Hong, L; Tapriyal, D; Kim, I; Paik, I; Crosthwaite, J; Hamilton, A; Thies, M; Beckman, E; Enick, R; Johnson, J (2009)
Ab initio molecular modeling is used to design nonfluorous polymers that are potentially soluble in liquid CO2. We have used calculations to design three nonfluorous compounds meant to model the monomeric repeat units of polymers that exhibit multiple favorable binding sites for CO2. These compounds are methoxy isopropyl acetate, 2-methoxy ethoxy-propane, and 2-methoxy methoxy-propane. We have synthesized oligomers or polymers based on these small compounds and have tested their solubility in CO2. All three of these exhibit appreciable solubility in CO2. At 25 degrees C, oligo(3-acetoxy oxetane)6 is 5 wt % soluble at 25 MPa, the random copolymer (vinyl methoxymethyl ether30-co-vinyl acetate9) is 5 wt % soluble at 70 MPa and random copolymer (vinyl 1-methoxyethyl ether30-co-vinyl acetate9) is 3 wt % soluble at 120 MPa. These oligomers and polymers represent new additions to the very short list of nonfluorous CO2-soluble polymers. However, none of these are more soluble than poly(vinyl acetate), which exhibits the highest CO2 solubility of any known polymer containing only the elements C, H, and O.